2022
DOI: 10.1519/jsc.0000000000004365
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Loss Is Not an Accurate Predictor of the Percentage of Completed Repetitions During the Prone Bench Pull Exercise

Abstract: Pérez-Castilla, A, Miras-Moreno, S, Janicijevic, D, and García-Ramos, A. Velocity loss is not an accurate predictor of the percentage of completed repetitions during the prone bench pull exercise. J Strength Cond Res 37(5): 1001–1008, 2023—The primary aim of this study was to explore the goodness of fit and accuracy of both general and individual relationships between the magnitude of velocity loss (%VL) and the percentage of performed repetitions with respect to the maximal number of repetitions that can be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 31 publications
5
19
0
Order By: Relevance
“…Our findings are in line with previous studies that reported a moderate to strong goodness-of-fit for the general %rep-%VLT relationships obtained in several resistance training exercises ( R 2 ≥ 0.77) 6 7 10 11 12 13 26 . In addition, supporting our third hypothesis, the individual %rep-%VLT relationship provided a higher goodness-of-fit than the general %rep-%VLT relationship.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in line with previous studies that reported a moderate to strong goodness-of-fit for the general %rep-%VLT relationships obtained in several resistance training exercises ( R 2 ≥ 0.77) 6 7 10 11 12 13 26 . In addition, supporting our third hypothesis, the individual %rep-%VLT relationship provided a higher goodness-of-fit than the general %rep-%VLT relationship.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, supporting our third hypothesis, the individual %rep-%VLT relationship provided a higher goodness-of-fit than the general %rep-%VLT relationship. These results are in agreement with those demonstrated for the Smith machine bench press ( R 2 =0.97–0.99 vs. 0.80–0.94) 11 , Smith machine prone bench pull ( R 2 =0.84–1.00 vs. 0.74–0.85) 10 , and free-weight back squat ( R 2 =0.24–1.00 vs. 0.67–0.80) 14 exercises. For the reason explained above, these results are likely due to the high variability that exists across individuals in the pattern of repetition velocity decline during the training set.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with previous findings by Mor án-Navarro et al (17) who observed a narrow range for the absolute velocity thresholds corresponding to 2 (0.50-0.53 m•s 21 ), 4 (0.56-0.58 m•s 21 ), 6 (0.62-0.64 m•s 21 ), and 8 (0.67-0.69 m•s 2 1 ) RIR when all loading magnitudes were taken together (65, 75, and 85% 1RM) during the Smith machine prone bench pull exercise. The comparable accuracy could be explained because general RIR-velocity equations are affected by the high interindividual variability in the number of repetitions completed when reaching a given magnitude of velocity loss (7,21,22), while individual RIR-velocity relationships are more affected when the velocity decline from repetition-to-repetition moves away from linearity (7). In addition, the greater absolute errors for $2 RIR could be explained by the greater intraindividual and interindividual variability for repetition velocities far from momentary failure (6).…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a larger project investigating the feasibility of different velocity-based methods to control the proximity-tofailure during the Smith machine prone bench pull exercise. The results regarding the %Rep-%VL and RTF-velocity relationships have been published elsewhere (16,22), while in this study, we examined the possibility of estimating the RIR from velocity recordings. More specifically, to shed light on the importance of individualizing the RIR-velocity relationships, these relationships were constructed pooling the data from all subjects recruited for this study (general RIR-velocity relationship) as well as independently for each subject (individual RIR-velocity relationship).…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%